Characterization, Classification and Evaluation of Soils in Semi-arid Ecosystem of Chillakur Mandal in SPSR Nellore District of Andhra Pradesh - M.V.S. Naidu, U. Vedadri (Journal of the Indian Society of Soil Science, 2018)
Seven typical pedons representing major landforms in semi-arid ecosystem of Chillakur mandal in SPSR Nellore district of Andhra Pradesh viz., plains and uplands developed from granite-gneiss and alluvium parent material under varying land uses were studied for their morphological characteristics, physical and chemical properties and soil genesis. These soils were slightly acidic to moderately alkaline (pH 6.10 to 8.50) in reaction, non-saline, moderately deep to very deep, and had isohyperthermic temperature and ustic soil moisture regime. Texture, organic carbon (OC), cation exchange capacity (CEC) and base saturation ranged from sand to clay loam, 1.2 to 6.1 g kg-1, 4.70 to 25.52 cmol(p+)kg-1 soil and 54.0 to 98.2 per cent, respectively. Soils were low to medium in available N (59 to 439 kg ha-1 and P (8 to 30 kg ha-1), low to high in available K (78 to 327 kg ha-1) and high in available S ( 15 to 40 mg kg-1). The DTPA extractable Zn was deficient, whereas DTPA extractable Cu, Fe (except pedon 7) and Mn were sufficient. Pedons 1, 3, 4 and 7 were grouped under Entisols due to absence of sub-surface diagnostic horizon and were classified as Typic Ustorthents and Typic Ustipsamments whereas pedons 2, 5 and 6 were placed under Inceptisols due to presence of cambic (Bw) sub-surface diagnostic horizon and classified as Typic Haplustepts. All soils of the study area fall in agricultural land under land capability classes III and IV having limitations of slope and erosion. On the basis of major soil constraints and potentials, suitable land use plan for Chillakur mandal was suggested.